Cytotoxic effect of celastrol alone or in combination with paclitaxel on anaplastic thyroid carcinoma cells - Si Hyoung Kim; Jun Goo Kang; Chul Sik Kim; Sung-Hee Ihm; Moon Gi Choi; Hyung Joon Yoo; Seong Jin Lee (Tumor Biology, 2017)
The influence of celastrol alone or in combination with paclitaxel on survival of anaplastic thyroid carcinoma cells was investigated. In 8505C and SW1736 cells, after treatment of celastrol, cell viability decreased, and cytotoxic activity increased. The protein levels of heat shock protein (hsp) 90, hsp70, Bax, death receptor 5, cleaved caspase-3, cleaved poly (ADP-ribose) polymerase, phospho-extracellular signal-regulated kinase 1/2 (ERK1/2), and phospho-c-Jun N -terminal kinase (JNK) were elevated, and those of Bcl2, phospho-nuclear factor-kappaB (NF-κB), and total and phospho-Akt were reduced. The endoplasmic reticulum stress markers expression and reactive oxygen species production were enhanced. In celastrol-treated cells, N -acetylcysteine increased cell viability and phospho-NF-κB protein levels, and decreased reactive oxygen species production and cytotoxic activity. The protein levels of cyclooxygenase 2, phospho-ERK1/2, phospho-JNK and Bip were diminished. After treatment of both celastrol and paclitaxel, compared with paclitaxel alone, cell viability and the percentage of viable cells were reduced, and death rate and cytotoxic activity were elevated. The protein levels of phospho-ERK1/2, phospho-JNK, Bip, and cyclooxygenase 2, and reactive oxygen species production were enhanced. All of the Combination Index values calculated by Chou–Talalay equation were lower than 1.0, implying the synergism between celastrol and paclitaxel in induction of cell death. In conclusion, our results suggest that celastrol induces cytotoxicity through involvement of Bcl2 family proteins and death receptor, and modulation of phospho-NF-κB, Akt, and mitogen-activated protein kinase in association with endoplasmic reticulum stress and reactive oxygen species production in anaplastic thyroid carcinoma cells. Moreover, celastrol synergizes with paclitaxel in induction of cytotoxicity in anaplastic thyroid carcinoma cells.